PERBANDINGAN ASPEK ONTOLOGI DAN EPISTEMOLOGI ILM AL-MAâ€™ANIY DAN PRAGMATIK - Fauzi, Moch Sony (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2011)
The Maâ€™aniy and Pragmatics are two field of study that is closely related to language. Both of them have different background. The Maâ€™aniy was born from the intention to discover the miracle of Qurâ€™an from its language. On the other hand, pragmatics was born from the study of language phenomena in the forms of human utterances. The maâ€™aniy was born in eastern world, and pragmatics was from the west. Through contrastive analytic and conventional text study this paper is aimed at comparing the epistemological aspects of those two field of study, especially at three different aspects of pragmatics, theory of speech act, implicature and relevance. Those three aspects are found out the similarities with the aspects in maâ€™aniy. The findings are first, ontologically, there is similarity between maâ€™aniy and pragmatics, especially in discussing the forms and meaning of speech that is influenced by speech context. Many definitions of those two field of studies have similarities. Second, epistemologically, those two field of studies have similarities, for example, in maâ€™aniy there is â€œkalam khabariyâ€ and â€œkalam insyaâ€™iyâ€, that is similar to the maxim violation in the speech implicature in pragmatics.